Analysis of Separation of Organic and Inorganic Waste at the Agus Salim People's Market in Pekanbaru City in 2022: Analisis Pemilahan Sampah Organik Dan Anorganik Di Pasar Rakyat Agus Salim Kota Pekanbaru Tahun 2022 - Yoza Rismelia; Djasmudin Djalal; Kamali Zaman; Mishbahuddin Mishbahuddin; Benny Yulianto (Badnur Medisa Group, 2022)
Based on data from the National Waste Management Information System (SIPSN) in 2019, the waste generation in Pekanbaru City was 378,324.91 tons and the daily waste generation was 1,036.51 tons. Meanwhile, in 2020 there was an increase in waste generation in the city of Pekanbaru as much as 400,461.54 tons and waste generation per day as much as 1,097.15 tons. In 2021, the waste generation in Pekanbaru City is 323,032.45 tons and 885.02 tons per day. The purpose of this study is to determine the sorting of organic and inorganic waste at Pasar Rakyat Agus Salim in Pekanbaru City in 2022. This type of research is qualitative with a descriptive design, the informants in this study amounted to 6 people, namely 1 key informant, 2 main informants. and 3 supporting informants. The results of this study indicate that there is no prior separation between organic and inorganic waste before the waste is disposed of, organic and inorganic waste is combined in one place. The infrastructure used for waste sorting is inadequate, there are no trash bins for organic or inorganic waste, the cleaners do not wear masks, gloves, boots when transporting garbage. The regulations that apply at the Agus Salim market such as do not mix organic and organic waste, and also don't litter, traders have not complied with the regulations that have been set. There is no training for janitors to increase the knowledge of janitors regarding organic and inorganic waste sorting. Berdasarkan data dari Sistem Informasi Pengelolaan Sampah Nasional (SIPSN) Pada tahun 2019 timbulan sampah di Kota Pekanbaru sebanyak 378,324.91 ton dan timbulan sampah perharinya sebanyak 1,036.51 ton. Sedangkan pada tahun 2020 terjadi kenaikan timbulan sampah di kota Pekanbaru sebanyak 400,461.54 ton dan timbulan sampah perharinya sebanyak 1,097.15 ton. Pada tahun 2021 timbulan sampah di Kota Pekanbaru sebanyak 323,032.45 ton dan perharinya sebanyak 885.02 ton. Tujuan penelitian ini untuk mengetahui Pemilahan sampah organik dan anorganik di Pasar Rakyat Agus Salim di Kota Pekanbaru tahun 2022. Jenis penelitian ini adalah kualitatif dengan desain yang digunakan adalah deskriptif, informan dalam penelitian ini berjumlah 6 orang yaitu 1 orang informan kunci, 2 orang informan utama dan 3 orang informan pendukung. Hasil Penelitian ini menunjukkan bahwa tidak dilakukan pemilahan terlebih dahulu antara sampah organik dan anorganik sebelum sampah dibuang, sampah organik dan anorganik digabung didalam satu tempat. Sarana Prasarana yang di gunakan untuk pemilahan sampah belum memadai, tidak ada tempat sampah untuk sampah organik ataupun anorganik, petugas kebersihan tidak memakai masker, sarung tangan, sepatu bot saat mengangkut sampah. Peraturan yang di berlakukan di pasar agus salim seperti jangan mencampur sampah organik dan organik, dan juga jangan buang sampah sembarangan, pedagang belum mematuhi peraturan yang telah ditetapkan. Tidak ada pelatihan untuk petugas kebersihan untuk menambah pengetahuan petugas kebersihan terakit pemilahan sampah organik dan anorganik.